Korelasi Indeks Massa Tubuh dengan Kadar Kolesterol Total pada Mahasiswa Pre Klinik Fakultas Kedokteran Universitas Andalas - Zikra Muhammad; Julizar Julizar; Avit Suchitra (Jurnal Ilmu Kesehatan Indonesia, 2021)
The increase in body mass index is a condition were excessive increase in fat accumulation in adipose tissue so it can be detrimental to health. Increase in lipid metabolism can trigger the increase in cholesterol level inside the body. This study aimed to know the correlation between body mass index and total cholesterol level on Medical Faculty of Andalas University pre clinic student. The research method used in this study was an analytic cross sectional approach, conducted from April to December 2020 in Medical Faculty of Andalas University. The subject were 35 pre clinic students who currently in Padang when the research was conducted. The data taken in this research were age, sex, height, weight, and total cholesterol level. The statistical test used was Pearson correlation test. The result of this research found that p value was 0,173, showed that there was a meaningless relation between BMI and total cholesterol level with negative correlation value (r = -0,236). This research concludes that there is no correlation between BMI with total cholesterol level on Medical Faculty of Andalas University pre clinic student.